2022
DOI: 10.3390/cancers14010218
|View full text |Cite
|
Sign up to set email alerts
|

Microsatellite Instability, Epstein–Barr Virus, and Programmed Cell Death Ligand 1 as Predictive Markers for Immunotherapy in Gastric Cancer

Abstract: Immunotherapy benefits selected cases of gastric cancer (GC), but the correlation between biomarkers and prognosis is still unclear. Fifty-two patients with GC who underwent immunotherapy were enrolled from June 2016 to December 2020. Their clinical features and biomarkers—microsatellite instability-high (MSI-H), programmed cell death ligand 1 (PD-L1) combined positive score (CPS), and Epstein–Barr encoding region (EBER)—were analyzed. Eight patients had MSI-H, five patients had EBER, 29 patients had CPS ≥ 1, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 33 publications
1
10
0
Order By: Relevance
“…CheckMate-649 enrolled 1581 GC patients, and first-line nivolumab plus chemotherapy resulted in significant improvements in OS (hazard ratio [HR] 0.71, P < 0.0001) and PFS (HR 0.68, P < 0.0001) versus chemotherapy alone in patients with a PD-L1 CPS of five or more; moreover, additional results showed that the OS and PFS benefits were retained in patients with CPS ≥1% (HR = 0.77, P < 0.0001; HR = 0.74, retrospectively) [ 57 ]. Yu et al also found that MSI-H, EBER, and CPS are meaningful biomarkers for predicting the efficacy of immunotherapy, and combined biomarkers could differentiate better PFS ( P = 0.01) in patients with GC [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…CheckMate-649 enrolled 1581 GC patients, and first-line nivolumab plus chemotherapy resulted in significant improvements in OS (hazard ratio [HR] 0.71, P < 0.0001) and PFS (HR 0.68, P < 0.0001) versus chemotherapy alone in patients with a PD-L1 CPS of five or more; moreover, additional results showed that the OS and PFS benefits were retained in patients with CPS ≥1% (HR = 0.77, P < 0.0001; HR = 0.74, retrospectively) [ 57 ]. Yu et al also found that MSI-H, EBER, and CPS are meaningful biomarkers for predicting the efficacy of immunotherapy, and combined biomarkers could differentiate better PFS ( P = 0.01) in patients with GC [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…22,23 Immunotherapy produced a durable response in selective gastric cancer cases. 24 Thus, immunotherapy may be a treatment of choice for patients with GASC, particularly for those with a high positivity rate of prediction markers in the tumor.…”
Section: Discussionmentioning
confidence: 99%
“…Immunotherapy is approved in selected cases of gastric cancer, but the correlation between biomarkers and prognosis is still unclear ( 29 ). Several potential predictive biomarkers have been identified in some exceptional responders with gastric cancer, such as PD-L1, HER2, MMR, and EBER ( 1 , 30 , 31 ).…”
Section: Discussionmentioning
confidence: 99%